Global Increase in the Consumption of Lignocellulosic Biomass as Energy Source: Necessity for Sustained Optimisation of Agroforestry Technologies. (24th November 2011) - Erakhrumen, Andrew Agbontalor
Abstract : Wood and other nonwood lignocellulosic materials are renewable natural resources useful for different applications based on end users' preference. Their use for generating energy, an application that has not been outmoded, has been noted to be increasing worldwide owing to multifarious reasons. Therefore, there has been the need for studies with results targeted at sustainable ways by which they can be sourced for this and other purposes, as this source of energy is currently still relevant particularly in the developing world. Agroforestry techniques that are based on realisable concepts acceptable to stakeholders have been suggested for this purpose. These age-long techniques are adopted for different purposes with incorporated components partly dependent on native intelligence, indigenous/traditional knowledge, and/or users' perspectives and expected outputs. Since wood and other lignocellulosic biomass can be obtained using these production techniques, optimising their potentials in this regard will be beneficial. This paper was therefore focused on the increasing trend in global wood fuel consumption and studies aimed at contributing to improvement of agroforestry systems as sustainable sources of wood fuel, a renewable source of energy.